EFFECT OF NEW HERBICIDE MOLECULES ON YIELD, SOIL MICROBIAL BIOMASS AND THEIR PHYTOTOXICITY ON MAIZE (ZEA MAYS L.) UNDER IRRIGATED CONDITIONS - HATTI, VEERESH; M. T. SANJAY; PRASAD, T. V. RAMACHANDRA; MURTHY, K. N. KALYANA; KUMBAR, BASAVARAJ; M. K. SHRUTHI (The Bioscan, 2014)
A field experiment was carried out during kharif 2012 at Main Research Station, University of Agricultural Sciences, Hebbal, Bangalore, Karnataka to evaluate the effect of new herbicide molecules on yield, soil microbial biomass and their phytotoxicity on maize in sandy loam soil under irrigated conditions. The experiment was laid out in RCBD with fourteen treatments replicated thrice. The treatments were pre and post-emergence herbicides (atrazine, oxyflurofen, pendimethalin and topramezone, 2, 4-D, tembotrione, respectively) and their combinations (topramezone + atrazine with and without adjuvant) which were compared with farmer’s practices of intercultivation and hand weeding as well as weedy check. Significantly higher kernel yield was observed in preemergence application of oxyflurofen 23.5 EC – 200 g a. i. ha-1 at 3 DAS followed by post-emergence application of 2, 4-D Na salt 80 WP - 500 g a. i. ha-1 at 30 DAS (6107 kg ha-1) when compared to farmer’s practice of two inter cultivations (5418 kg ha-1), two hand weeding (6081 kg ha-1) and weedy check (2157 kg ha-1). And the soil microbial biomass in herbicide treated treatments was significantly reduced at 25 DAS in comparison to sowing. However at harvest the soil microbial biomass was recovered due to degradation of herbicide. All these herbicides were not having any phytotoxic effect on the crop